Supporting Victims of Hate Crime : A Practitioner Guide - Chahal, Kusminder (Book collections on Project MUSE., 2017)
« This practical guide provides user-friendly, concise, expert and up-to-date guidance for both new and experienced hate crime caseworkers and advocates (whether professional or volunteers). Filling a gap in the growing debates and research literature on hate crime, it takes as its starting point a values-based casework practice that provides assistance, support and leads to the empowerment of victims of hate crimes. With core casework standards and guidance on how to respond from a person-centred approach to the victim's perspective, it also provides an overview of current legislation in relation to prosecuting hate crimes and the current EU Directive on victim support. Full of relevant, up-to-date evidence based research and policy, it will enable practitioners to be confident and knowledgeable in supporting victims of hate crime. »--